P21 Does time of day affect outcomes on an advanced office based driving simulator in patients with obstructive sleep apnoea syndrome (OSAS)?. (2nd December 2011) - Ghosh, D; Jamson, S L; Baxter, P D; Elliott, M W
Abstract : Introduction: Road traffic accidents (RTA) are known to peak at certain times of the day especially early afternoons. OSAS patients are at higher risk of being involved in RTA. Recently we have established that it is possible to identify with high degree of certainty a group of OSAS sufferers who perform significantly worse than others using specific simulator parameters on our advanced office based driving simulator (miniSim). We now explore whether the time of day when the study is performed affects simulator outcomes. Methods: 205 (52±10 yrs, ESS 12±5, AHI 33±22) patients performed a 90 km motorway driving scenario on the miniSim. Two events were programmed to trigger evasive actions, one subtle (Veer event) where an alert driver should not crash, while with the other (Brake event) even a fully alert driver might crash. There were three possible outcomes of the simulator runs; "fail", "indeterminate" and "pass". "Fail" was defined by any crash other than at the brake event and/or inability to complete the test. Comparisons were made between the patient populations performing the test before & after 12:00 in terms of demographics, symptoms & severity of OSAS. Outcomes on the simulator, lane position & reaction times were also compared between these groups. Results: There were no differences between the patients performing at the different time slots in terms of age, BMI, ESS & AHI (Abstract P21 table 1 ). The number of "fails", "indeterminates" & "passes" during morning & afternoon runs were: 16/26/70 (n=112) & 22/30/41 (n=93). Patients performing in the afternoon were no more likely to fail the test than those doing it in the morning (Fisher's exact test p=0.1). There were no differences in terms of lane position or reaction times (p=0.38, 0.65). Conclusion: The results indicate that the time of day the study is performed is unlikely to affect outcomes on this driving simulator. It has implications for its clinical use as the test can performed at any time of the day.